Blending polymer-sulfur coated and NBPT-treated urea to improve nitrogen use efficiency and grain yield in corn production systems - González Villalba, Hugo Abelardo (2018)
Blends of controlled release and stabilized nitrogen (N) fertilizer represent an alternative to provide N at all corn growth stages, and is an option to reduce costs compared to the use of solely controlled release N. In this context, field experiments were conducted in Southeast Brazil with the use of a blend of polymer-sulfur coated urea (PSCU) and NBPT-treated urea (NBPTU) at a 70:30 ratio, applied at corn planting and incorporated into the soil. The objectives of the study were: i) to quantify and measure each fertilizer-derived N fate in the plants, and determine the nitrogen recovery efficiency of each N source in the blend; ii) to evaluate corn grain yield response to N rates (blend) in contrasting cropping systems, and to assess the posibility of reducing N rate when applying a blend of two enhanced efficiency N fertilizers compared to the application of regular urea; iii) understand and monitor changes in plant biomass and N uptake during the growing season. Fertilizer N contributed with less than 50% of the total plant N uptake at all evaluated corn growth stages (V4, V12, R2, and R6). At V4 growth stage, most of the N in the plant derived from fertilizer (NPDF) was provided by NBPTU, while later in the season, most of the NPDF was provided by PSCU. At harvest, most of the plant N was allocated in the grains (59%). Of the total plant N, 64% was supplied by the native soil N pool, 26% was provided by PSCU, and 10% by NBPTU. Therefore, NBPTU provided N to corn early in the season, while PSCU played a crucial role supplying N later in the season, as plants demand for N increased. Soil N was the main N source at all GS and this fraction decreased as N rate increased. At harvest, 64% of the total plant N was derived from the soil native N pool, 26% derived from PSCU, and 10% from urea. The measured fertilizer NRE of urea was in average 36%, and the estimated NUE from PSCU was 51%. In the second study, corn grain yield varied between sites, probably due to soil and climate characteristics of each site. Corn grain yield, N uptake, and biomass production were greatly impacted by fertilizer N. Grain yield and N uptake showed a quadratic response to N rates (blend). The blend of PSCU and NBPTU, applied at corn planting and incorporated into the soil proved to be a great strategy to attain yields at N rates below those needed when using regular urea. The third chapter focused on corn biomass and N uptake and partitioning throughout the growing season, and it was demonstrated that the amount of N uptake after flowering can reach up to 50% of the total plant N, thus, N availability must be guaranteed in late vegetative corn growth stages, and especially in the reproductive stages, which can be achieved by adopting enhanced efficiency N fertilizers such as the blend of PSCU and NBPTU used in this study.